2021
DOI: 10.1186/s40816-021-00298-w
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary toxicology profile of Dennettia tripetala (Pepper Fruit) methanolic leaves extract

Abstract: Background Dennentia tripetalla (Pepper Fruit) belongs to the Annonaceae family and is abundant in Nigeria. Its fruit in folklore medicine is used for treatment of varying ailments. While ample research evidence exists on the plants fruit and seed, no current study exists on the toxicological profile of the plant leaves. Methods qualitative and quantitative phytochemicals and In vitro antioxidant assays were carried out using standard methods. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 46 publications
1
6
1
Order By: Relevance
“…Our study showed a decline in GPx activity following oral administration of DM in the brain of mice, thus indicating a reduction in the brain's ability to combat H2O2 created due to oral administration of DM. Subsequent studies stated that GPx protected against doxorubicin-induced apoptosis [ 50 , 51 ] and could also protect against cell death in response to cytotoxic drugs, which was contrary to the findings of this study, wherein DM exposure depleted Gpx activities in mice [ 52 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Our study showed a decline in GPx activity following oral administration of DM in the brain of mice, thus indicating a reduction in the brain's ability to combat H2O2 created due to oral administration of DM. Subsequent studies stated that GPx protected against doxorubicin-induced apoptosis [ 50 , 51 ] and could also protect against cell death in response to cytotoxic drugs, which was contrary to the findings of this study, wherein DM exposure depleted Gpx activities in mice [ 52 ].…”
Section: Discussioncontrasting
confidence: 99%
“…While CAT activity, revealed a non-significant distinction after treatment with Ag NPs and Ag-I NPs. The increase in GPx activity may have occurred in response to boost immunity of the animals or a complementary mechanism to support the elimination of free radicals from the system [38]. Ag NPs may have enhanced GPx to suppressed oxidative stress in-vivo by maintaining hydrogen peroxide at a low level and modulating mechanisms involved in wound healing process such as blood clotting, thrombosis, angiogenesis, migration and fibrosis [39].…”
Section: Haematological Studiesmentioning
confidence: 99%
“…The increased activities of catalase in the Cd and co-exposure group as well as increased SOD activities in the coexposure group may have occurred in response to mop up of rising peroxides and other reactive oxygen and nitrogen species which may have been elicited by these metals [72,73]. Catalase and SOD being antioxidant enzymes are well known as key responders in the presence of prooxidants and hydroxyl radicals [74,75]. The observed rise therefore, are in tandem with earlier results on the ability of these metals to induce increased activities of these enzymes [76,77].…”
Section: Discussionmentioning
confidence: 98%